Pharmacological Evaluation of Caesalpinia pulcherrima Leaf Extract for Anticancer Activity against Ehrlich Ascites Carcinoma Bearing Mice - Mallapur, Shamanand; Biradar, Prakash Rajshekhar; Kavatagimath, Satish Annayya; Patil, Priyanka; Patil, Vishal; Kudatarkar, Namit (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The aim of the study is to assess the anticancer activity of Caesalpinia pulcherrima leaf extract against Erlich Ascites Carcinoma (EAC) in mice. Materials and Methods: BALB/c mice with Erlich Ascites Carcinoma were used for the present study. Ethanolic extract of C. pulcherrima (EECP) was administered p.o. in three different doses i.e. 200, 400 and 800 mg/kg body weight, after 24 hr of tumor inoculation in mice for 14 days. Effect of EECP on haematological parameters, liver enzymes marker, biochemical parameters/ antioxidants was evaluated after 14 days treatment. Results: Effect of EECP on Haematological parameters were evaluated and Hb, Lymphocytes, RBC and Monocytes showed significant increase in their count when compared to Disease. WBC and neutrophil count was decreased in EECP group compared to disease. Effect of EECP on Serum parameters were evaluated and showed significant decrease in ALP, TC, AST, ALT and TG compared to disease. TP was significantly increased in EECP groups compared to DISEASE group. Effect of EECP on Antioxidant activity showed significant increase in CAT, SOD, GSH and GPx counts compared to Disease. LPO level was significantly reduced in all the treated groups compared to Disease group. Conclusion: Ethanolic extract of C. pulcherrima leaf exhibited significant antioxidant and anticancer activity against Erlich Ascites Carcinoma.
Keywords: Anticancer; Antioxidant; Caesalpinia pulcherrima; EAC; Malignancy